Exploring mineralisation potential using geophysical, remote sensing and field studies in parts of the Migmatite-Gneiss complex, Kwara State, Nigeria - ALI, Abdullah Musa; AMINU, Ahmed Alhassan (Contributions to Geophysics and Geodesy, 2025)
Gold mineralisation and enrichment of critical minerals can be found in placers and veins in the schist belts of the western part of Nigeria. The study area, Bielesin, Asa in Kwara State, experiences a preponderance of artisanal mining that targets the primary gold-quartz presence and associated alluvial occurrences due to the lack of any methodical exploration and development. Hence, this study focuses on preliminary exploration in the study area, which entails identifying geological indicators of mineralisation, and deploying gravity survey and remote sensing investigations to determine potential mineralisation structures. Geochemical analysis was utilised to determine the trace elemental composition of the samples. Vertical electrical sounding (VES) was used to ascertain the thickness of the deposit. The identified minerals in the migmatite gneiss include quartz, feldspar and tourmaline. The observed folded gneissose foliation, schollen and stromatic folds, pegmatites and quartzo-feldspathic veins, and lenses of biotite are indicative of anatexis, which allows for the formation of pegmatites. The valuable minerals occur as discrete grains disseminated in pegmatite and veins. The geological controls for the hosting and emplacement of the mineralisation are structural (faults, fractures). Several features were detected in the study area that could serve as structural controls for ore deposition from hydrothermal solutions or ascending magmatic intrusions. From the interpretation of 3D Euler deconvolution and resistivity results as well as the trenching, the potential auriferous mineralised zones extend from the low-lying quartz veins and pegmatites at depths of approximately 1 m to deep-seated mineralisations at >1000 m. This could help in tonnage estimation and the determination of equipment requirements for excavation activities. This study suggests the presence of gold mineralisation in the study area.